Classification of Ultrasound-Based Breast Cancer Images with Deep Learning Approaches - Ateş, Feyzi Ferat; Çalışkan, Abidin; Toğaçar, Mesut (Fırat University, 2022)
Breast cancer is one of the most common types of cancer among women. As with other types of cancer, early diagnosis is important in the treatment of breast cancer patients. Recently, artificial intelligence has made its name in many fields. In the field of health, artificial intelligence has started to be used as a technological infrastructure in diagnosis and treatment processes. In this study, an artificial intelligence-based approach that can diagnose breast cancer using ultrasound-based images is proposed. The proposed approach consists of pre-trained convolutional neural networks. A new fully connected layer is added to the last layer of each convolutional neural network. The feature that distinguishes the fully connected layer from the previous fully connected layers is that it gives as many features as the number of input types. Then, the classification process was carried out by combining the fully connected layers of the convolutional neural networks. In this study, a triple classification process was carried out as benign, malignant and normal. As a result of the experimental analysis, 99.57% overall accuracy was achieved with the proposed approach. The proposed approach outperformed the convolutional neural network models used in the experiment.

Meme kanseri bayanlar arasında en sık görülen kanser türlerinden biridir. Diğer kanser türlerinde olduğu gibi meme kanseri hastalarının tedavisinde erken tanı önemlidir. Son zamanlarda yapay zekâ birçok alanda adını duyurmuştur. Sağlık alanında da yapay zekâ tanı ve tedavi süreçlerinde teknolojik alt yapı olarak kullanılmaya başlamıştır. Bu çalışma da ultrason tabanlı görüntüler kullanılarak meme kanseri teşhisini gerçekleştirebilecek yapay zeka tabanlı bir yaklaşım önerilmektedir. Önerilen yaklaşım önceden eğitilmiş evrişimsel sinir ağlarından oluşmaktadır. Her bir evrişimsel sinir ağının son katmanına yeni bir tam bağlantılı katman eklenmiştir. Tam bağlantılı katmanı önceki tam bağlantılı katmanlardan ayırt eden özelliği girdi türü sayısı kadar öznitelik vermesidir. Ardından evrişimsel sinir ağlarının tam bağlantılı katmanları birleştirilerek sınıflandırma işlemi gerçekleşmiştir. Bu çalışmada iyi huylu, kötü huylu ve normal olmak üzere üçlü bir sınıflandırma işlemi gerçekleşmiştir. Deneysel analiz sonucunda önerilen yaklaşım ile %99,57 genel doğruluk başarısı elde edilmiştir. Önerilen yaklaşım deneyde kullanılan evrişimsel sinir ağı modellerinden daha iyi performans göstermiştir.
Ultrason Tabanlı Meme Kanseri Görüntülerinin Derin Öğrenme Yaklaşımları ile Sınıflandırılması